Enzymatic control of cysteinyl thiol switches in proteins - Deponte, Marcel; Lillig, Christopher Horst (Biological chemistry, 2015)
Abstract The spatiotemporal modification of specific cysteinyl residues in proteins has emerged as a novel concept in signal transduction. Such modifications alter the redox state of the cysteinyl thiol group, with implications for the structure and biological function of the protein. Regulatory cysteines are therefore classified as ‘thiol switches’. In this review we emphasize the relevance of enzymes for specific and efficient redox sensing, evaluate prerequisites and general properties of redox switches, and highlight mechanistic principles for toggling thiol switches. Moreover, we provide an overview of potential mechanisms for the initial formation of regulatory disulfide bonds. In brief, we address the three basic questions (i) what defines a thiol switch, (ii) which parameters confer signal specificity, and (iii) how are thiol switches oxidized?
Gesehen am 13.01.2021